Vaccination of Children with Hemoblastosis - M. P. Kostinov; A. A. Tarasova (Эпидемиология и вакцинопрофилактика, 2017)
Recommendations highlighted features vaccination children with hemoblastosis It is shown how the immunization scheme may be changed according to the pathology and the age of the child.